UNDERSTANDING DIGITAL TRANSFORMATION FROM A DIGITAL-BASED DYNAMIC CAPABILITIES PERSPECTIVE: A CASE STUDY FROM INDONESIA LIFE INSURANCE INDUSTRY (Revista de Investigaciones Universidad del Quindío, 2022)
This qualitative study aimed to explore the current state of Indonesian life insurance companies’ digital transformation experiences and their dynamic capabilities to adapt to the Indonesian life insurance industry via digital technology. The study specifically examined the digital transformation experiences of the leadership team in life insurance Indonesia. The unit of analysis was at the life insurance company level, with CEOs and Board of Directors (BOD) as target informants. This study identified three critical themes associated with the relevant capabilities: developing the optimal customer journey, earning trust, and critical challenges as essential success factors for developing and exercising the capabilities mentioned above. The study identified a debate between two large senior management groups regarding the advantages and disadvantages of using a lifestyle approach as an engagement strategy to improve the transactional relationship between customers and insurance companies. This study has contributed to the field by providing researchers with helpful information. Not only is digital transformation a must to have in the Indonesian life insurance industry but it also demonstrates the importance of promoting life insurance, not as a product, but by treating insurance as a concept of life and protection. The study demonstrates the importance of earning trust contributed by the professionalism of the sales forces, the security of the digital process, and the positive customer journey. This study highlighted the need for regulators to collaborate with the industry regarding literacy, oversight, and key challenges. Finally, this study identified further research opportunities on the right lifestyle strategy and replication of this concept in other industries
Keywords: Dynamic Capabilities; Digital Transformation; Life Insurance; Lifestyle; Financial Literacy